The Effect of Using ChatGPT (Generative Pre-Trained Transformer) and Gemini AI (Artificial Intelligence) on the Laziness of Thinking of Islamic Religious Education Students at the State Islamic University of Sulthan Thaha Saifuddin Jambi in the Process of Working on Assignments - Lala Rahayu Winara; Ahmad Ridwan; Muhamad Taridi (MASI Mandiri Edukasi, 2026)
The use of generative AI such as ChatGPT and Gemini AI among Islamic Religious Education (PAI) students at UIN STS Jambi offers task efficiency, but has the potential to trigger laziness in thinking through cognitive offloading and disrupt the internalization of thinking, contemplation, and tazkiyah. This study aims to analyze the partial and simultaneous effects of both AIs on laziness in thinking and completing thesis assignments. A quantitative quasi-experimental posttest-only control group approach was used with a population of 5th-semester PAI students (N≈100), a sample of 56 respondents (experimental n=25, control n=31) via purposive sampling. The Likert questionnaire instrument was validated by Pearson and Cronbach's reliability α>0.70; SPSS analysis: descriptive, t-test, multiple linear regression (F/t test, R²). Results: Gemini AI had a significant effect (p<0.01, β=0.919), ChatGPT did not (p>0.05); Simultaneous R²=0.877 (p<0.01), t-test p=0.01 (d=0.72). Conclusion: The differential impact of multimodal AI strongly triggers laziness; an ethical strategy is needed for PAI to integrate AI as a reflection aid.